P3PM Poster Improves Knowledge and Attitudes Toward Personal Hygiene of Food Handlers at SPPG A - Fadlan Widyananda; Putri Ronitawati (ScieClouds Publishing, 2026)
Effective educational interventions are necessary to ensure food safety in the Free Nutritional Meal Program (MBG) by promoting personal hygiene among food workers. The purpose of this research is to examine how nutrition fulfillment service unit (SPPG) A food handlers' knowledge and attitudes toward personal hygiene were affected by counseling that made use of the P3PM posters (Personal Hygiene, Use of PPE, and Handwashing Practices for Food Handlers). A pre-experimental design with a one-group pre-test-post-test layout was utilized in this investigation. Thirteen food handlers chosen at random using a complete sample method made up the study's subjects. Before and after the intervention, data was collected using a knowledge and attitude questionnaire. Installation of three A3-sized P3PM posters in the food processing area and 45 minutes of counseling comprised the intervention. The results demonstrated that food handlers' expertise increased following the intervention, as evidenced by a change from adequate to good. Counseling also led to an 8.9 point improvement in food workers' attitudes about personal cleanliness. The results of the statistical analysis demonstrated a notable change in both knowledge and attitudes from the pre- to post-intervention periods (p0.005). The results show that food handlers in SPPG A can benefit from counseling using P3PM posters in terms of both knowledge and attitude.